New insights on the synergetic removal of nutrients and sulfonamides in solid carbon/manganese ore supported denitrification system: 1Water quality, microbial community and antibiotic resistance genes - Jia, Lixia; Wu, Weilong; Qi Zhou; Li, Yuanwei; Wu, Weizhong (CHEMICAL ENGINEERING JOURNAL, 2022)
The solid carbon source (poly-3-hydroxybutyrate co 3 hyroxyvalerate, PHBV) and manganese oxide mineral (Mn ore) were proposed firstly as co-substrates for eliminating nutrients and sulfamethoxazole (SMX) in this study. Results showed that high-rate nitrate and phosphate removal could be achieved in PHBV/Mn ore systems with the average efficiencies of 90% and 66.7%, respectively, although the addition of SMX decreased denitrification performance by 4.5-10.5%. SMX was removed mainly via biodegradation of enriched denitrifying microbes, with the average removal efficiency of 20-50% in PHBV/Mn ore systems, which was higher than that in PHBV systems. The existence of Mn ore markedly shaped the microbial community structure, leading to the dominant bacteria transforming from Microscillaceae to Sporomusaceae. The genera of Geobactor, Desulfovibrio and Anaerovorax were found to maintain the stability of microbial system as keystone species. Surprisingly, large amount of Mn(II) was accumulated, which not only verify the involvement of Mn cycling in decontamination process, but also might explain the propagation of ARGs (tnpA-04 and tnpA-05) in host microorganisms. Therefore, the optimized mixture proportion of PHBV and Mn ore should be further estimated avoiding Mn (II) accumulation in the effluent. On the whole, these results might shed light on new insight for advanced treatment of nutrients and emerging pollutants in biofilm reactors.